2012
DOI: 10.1007/s00449-012-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptogenic effects of Tricholoma giganteum on Ehrlich’s ascites carcinoma cell

Abstract: This study explored the efficacy of Fa fraction of Tricholoma giganteum against Ehrlich's ascites carcinoma (EAC). Mechanisms of apoptogenic effect of the fraction were delineated. The flow cytometric analysis of EAC cells, showed an increase in number of cells in sub-G(0)/G(1) population and reduction in the G(2)/M phase due to the treatment thus suggesting apoptosis. The induction of apoptosis has also been confirmed by nuclear staining that demonstrated distinctive morphological features of apoptosis. Our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The up-regulation of Bax might restrict the entry of cells into S-phase and can promote nuclear DNA fragmentation (Widlak, 2000). The result shows that treatment with MEZA decreased Bcl-2 and simultaneously increased Bax levels, resulting in the decrease of Bcl-2/Bax ratio (Chatterjee et al, 2013). The balance between the pro-and anti-apoptotic proteins thus shifted towards apoptosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The up-regulation of Bax might restrict the entry of cells into S-phase and can promote nuclear DNA fragmentation (Widlak, 2000). The result shows that treatment with MEZA decreased Bcl-2 and simultaneously increased Bax levels, resulting in the decrease of Bcl-2/Bax ratio (Chatterjee et al, 2013). The balance between the pro-and anti-apoptotic proteins thus shifted towards apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…MEZA (2 g/kg) was administered orally to male Swiss albino mice to evaluate the acute toxicity as per the reported method (Chatterjee et al, 2013).…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Mushrooms can grow very easily during the growing season and it is cultivated also in mass amount nowadays, so they are easily available. Those novel bioactive compounds from mushrooms have shown several pharmacological activities like anti-oxidant, 5 antimicrobial, 6 anticancer, 7 immuno-modulatory, 8 anti-diabetic, 9 anti-ulcer, 10 cardio-protective 11 and hepato-protective 12 etc. Free radicals are extremely reactive and highly unstable molecules with an unpaired electron.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that free radicals are the major cause of various chronic and degenerative diseases, such as coronary heart disease, inflammation, stroke, diabetes mellitus, and cancer [4]. Studies have shown that mushrooms have hepatoprotective [5][6][7], anticancer [8][9][10], antimicrobial [11,12], and antidiabetic [13,14] activities. A study of ancient literature indicates that diabetes (Madhumeha/Prameha) was fairly well-known and well-conceived as an entity in India.…”
Section: Introductionmentioning
confidence: 99%